Chemoprevention of Gastric Cancer: Metformin - Young-Il Kim; Soo-Jeong Cho (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Metformin is a first-line anti-diabetic drug that has been widely used in patients with type 2 diabetes. Many population-based epidemiologic studies have shown that metformin treatment is associated with decreased risk for various cancers. Recent epidemiologic studies showed that the use of metformin was associated with a reduction in gastric cancer risk, especially in patients with type 2 diabetes who used metformin for long periods of time (>2∼3 years). Currently, there are no registered clinical trials investigating the anti-cancer effect of metformin in gastric cancer; hence, further well-designed clinical trials are required. Herein, we review the literature regarding the use of metformin for the prevention of gastric cancer.